Intracapsular disorders of temporomandibular joint: from semiology to therapeutic: a literature review (Research, Society and Development, 2021)
Introduction: Temporomandibular disorders (TMD's) are conditions capable of directly affecting the anatomy and functional characteristics of the temporomandibular joint (TMJ). They can be classified according to the structures affected in: Muscular Dysfunction or extracapsular TMD, when it involves components of the masticatory system such as the muscles and Joint Dysfunction or intracapsular TMD, when it directly affects the TMJ. Objective: This work consists of a literature review that aims to describe etiological factors, symptoms, clinical signs, diagnostic methods and existing treatment modalities for TMJ intracapsular disorders. Methodology: A search was conducted in the electronic databases: PubMed, SciELO and Google Scholar, through the tracking of articles published between 2005 and 2020, in addition to books considered useful for the content of this study. Results: Intracapsular TMJ disorders are associated with a multifactorial etiology and may present symptoms and clinical signs similar to each other, for example, orofacial pain of varying intensity, limited jaw movements and joint noise. Imaging exams are decisive for the clinical diagnosis of disorders. Regarding treatments, conservatives are recommended and, if they do not show efficacy, surgical techniques are recommended. Conclusion: the role of the dentist in the primary care of patients with TMD is essential for a better therapeutic prognosis, reflecting, above all, in reducing the chronicity of the disease, since the early diagnosis and the beginning of a treatment that induces the adaptation of the disease. articulation in the face of disorders can prevent progression to more severe clinical conditions, such as degenerative diseases.